نظرات في اللسانيات العربية عند عبد الرحمان الحاج صالح وأثرها في المباحث اللغوية ذات الصلة بعلوم القرءان - عبد المؤمن, بلباز; رضوان, لخشين (جامعة الوادي university of eloued, 2023)
عتبر التكامل الموجود بين العلوم الإنسانية من أهم المرتكزات التي تعين على الإحاطة بالإشكاليات العلمية أو العملية التي تتصل بحياة الإنسان الفكرية ، وكل من العلوم الإنسانية تستمد حيويتها وتطورها من حيوية وتطور اللغة ، ومن هذا المنطلق كان الحكم على جودة الدراسات الإنسانية تابع لما مدى جودة البحث في الدراسات الألسنية ، وفي هذا المقال الذي يأخذ دراسات الأستاذ عبد الرحمان الحاج صالح كنموذج معتدل للدراسات اللسانية العربية ، ويأخذ بعض المباحث اللغوية القرءانية كنموذج للدراسات الإسلامية ، يهدف إلى معرفة المباحث المشتركة بينهما وماهية التكامل بينهما ، وكذا سبل التجديد لبعض من علوم القرءان على أساس النظرة المعاصرة التي تميزت بها بحوث الأستاذ عبد الرحمان الحاج صالح. : The integration that exists between the human sciences is one of the most important foundations that help to understand the scientific or practical problems related to the intellectual life of human, and each of the human sciences derives its vitality and development from the vitality and development of language, From this point of view, the judgment on the quality of human studies was dependent on the extent of the quality of research in linguistic studies, and in this article, which takes the studies of Professor Abd al-Rahman al-Haj Saleh as a moderate model for Arabic linguistic studies, And it takes some Qur'anic linguistic researches as a model for Islamic studies, aiming to know the common topics between them and the nature of their integration, as well as the ways to renew some of the sciences of the Qur’an on the basis of the contemporary view that characterized the research of Professor Abd al-Rahman al-Haj Saleh
مقال
Keywords: علوم القرءان ; اللسانيات ; الأثر